Method for barometers calibration based on radiosonde observations - Hidalgo, Luis (Rev. Téc. Fac. Ing. Univ. Zulia)
A new method to calibrate fixed and portable barometers is described and tested: The method is based on data from the World Net of Radiosonde (WNR). The World Meteorological Organization (WMO) coordinates the WRN operations. A demonstration of the method that includes the calibration of a pair of barometers used jointly gave a standard estimation error of Ó0.49 hPa (1014-779 hPa). The level of that error permits the use of the pair in meteorological applications. An additional test of validation was undertaken successfully. The method was developed for the continental equatorial area of South America, although, there is no restrictions to its use in other tropical areas covered by the WNR.